IMPERIUM INTRA TERMINOS AND ITALIA DISCRIPTA - Federico De Romanis (Bollettino della Società Geografica Italiana, 2019)
Augustus’ skill in interpreting geographic space is apparent from the way he managed to shape his empire. Characterized by hegemonic pretentions of ecumenical proportions, but circumscribed within a realistic radius of government, the Augustan empire revolved around Italy, which was then extended up to the Alps and divided into eleven regiones. However, Augustan discriptio was not invented from scratch. It followed a pattern that was familiar to the Roman administration at least as early as the 3rd century BCE. Moreover, the numbering of the eleven regiones was based on a southup oriented mapping of the peninsula, which must have been widespread in the Roman culture, possibly long before Augustus.